Productivity Dynamics and the Role of Big-Box Entrants in Retailing - Florin Maican; Matilda Orth (Research Institute of Industrial Economics (IFN), 2012)
Entry of large (big-box) stores along with a drastic fall in the total number of stores is a striking trend in retail markets. We use a dynamic structural model to estimate retail productivity in a local market setting. In particular, we provide a general strategy of how to measure the causal effect of entry of large stores on productivity separate from demand. To control for endogeneity of large entrants, we use political preferences. Using detailed data on all retail food stores in Sweden, we find that large entrants force low productivity stores to exit and surviving stores to increase their productivity. Productivity increases most among incumbents in the bottom part of the productivity distribution, and then declines with the productivity level of incumbents. When controlling for prices, the impact of large entrants on productivity increases substantially. Our findings suggest that large entrants play a crucial role for driving productivity growth.
Keywords: C24; L11; O30; 330; Retail markets; Imperfect competition; Industry dynamics; Productivity; Dynamic structural model; Lebensmitteleinzelhandel; Unvollkommener Wettbewerb; Produktivität; Dekompositionsverfahren; Schweden